Assistance in Making Decoupage and Marketing through Online Media - Sriwartini, Yayu; Radjagukguk, Djudjur Luciana; Masnah, Masnah (Universitas Nusantara PGRI Kediri, 2019)
Decoupage creativity training assistance and effective marketing techniques through online media (especially social media) are given to street children in the hope of increasing their skills as a provision to find alternative sources of income. This training was provided to the children assisted by the Singgah Taruna Pertiwi House which is located at Pasar Minggu and the Rumah Pertiwi Shelter House on Jl. Bacang, Salihara. The two shelters are the choice because we want to contribute to street children who are built not far from the National University. Decoupage training activities are an option because it is a skill that is easy to learn. In addition to making decoupage training, the participants were also given effective marketing technique training through online media. The consideration is because nowadays online media has become a primary need and is the fastest and most effective and efficient medium for conducting promotions or marketing. In addition, it is cheap because it does not need to pay as much as if promotion through conventional media The first training activity lasted for approximately two months starting from May 26 to July 14, 2018, by producing decoupage works made on cutting board media, pouches of calico cloth and woven fans. The technique given is only at the initial stage, which is just putting tissue on the media. As long as the accuracy, accuracy, and neatness, then the results will look attractive and have a high selling value and aesthetics.